Comparative Analysis of Wind Speed And Direction Measurements From Sentinel- 1 SAR And Sentinel - 3 Satellites - Kalogirou, Eleftheria; Melillos, George; Mettas, Christodoulos; Evagorou, Evagoras S.; Hadjimitsis, Diofantos G. (My University, 2024)
This study focuses on the comparison of wind direction and speed between two satellites, Sentinel -1 SAR and Sentinel-3, using satellite data with a study area Southwest of Cyprus. While Sentinel 3 relies on sea surface anemometers, Sentinel 1 SAR uses radar for its measurements. The differences in results between the two satellites offer important insight into measurement methods and the use of satellite data in meteorology. The direction and speed of the wind is vital for marine safety and the prevention of hazards during navigation and marine surveys. Satellite observations provide important information, making this study critical for predicting and responding to marine hazards. Thus, understanding the differences between the wind measurements from Sentinel - 1 SAR and Sentinel - 3 is crucial to developing effective forecast models and achieving improved marine safety.
Keywords: Wind speed; Satellites; Synthetic aperture radar; Environmental monitoring; Safety; Wind measurement; Data modeling